Agrarian Citizenship and the Protection of Farmers' Rights in Indonesia's Forest Areas - M. Nazir Salim; Rahardian Rahmansani; Rohmat Junarto (Faculty of Law, Universitas Sebelas Maret, 2025)
The Ministry of Forestry designates Cimrutu Village, Central Java, Indonesia, as a forest area under the